THE RELATIONSHIP BETWEEN STUDY HABITS AND STUDENTS’ ACADEMIC ACHIEVEMENT IN DETAILED BUILDING DRAWINGS COURSE SEMESTER JANUARY-JUNE 2014 IN CIVIL ENGINEERING DEPARTMENT FT UNP - 451-459 , Ahmad Zikri (Universitas Negeri Padang, 2015)
Abstract This research was motivated by the number of students who score low in Detailed Building Drawings course and their poor study habits, including habits in arranging study plan and schedule, attending classes, reinforcing courses, and facing examination. This study aimed to determine the relationship between study habits and students’ academic achievement in Detailed Building Drawings course semester January-June 2014 in Civil Engineering Department, Faculty of Engineering of the State University of Padang.The type of this research is a correlational research. The population of this research is students majoring Civil Engineering who took Detailed Building Drawings course in semester January-June 2014. Samples were taken by using Taro Yamane formula. Independent variable (variable X) is study habits of students, and dependent variable (variable Y) is students’ academic achievement.From analysis of correlation, r value of 0.064 with Sig. (2-tailed) 0.651 was obtained. This value is greater than 0.05, means that there is no relationship between study habits and students’ academic achievement in Detailed Building Drawings course semester January-June 2014 in Civil Engineering Department, FT UNP. Compared with other relevant research that show significant contribution of study habits to academic achievement, it can be concluded that study habits do not affect academic achievement in practical courses. This research is recommended for the students to review more and practice to draw at home because Detailed Building Drawings is a kind of dominant practice course which needs the students’ ability and creativity in drawings. Keywords : Relationship, Study Habits, Academic Achievement